Quality of life among people with mental illness attending a psychiatric outpatient clinic in Ethiopia: a structural equation model - Alemu, Wondale Getinet; Mwanri, Lillian; Due, Clemence; Azale, Telake; Ziersch, Anna (Frontiers in Psychiatry, 2024)
Background Mental illness is one of the most severe, chronic, and disabling public health problems that affects patients’ Quality of life (QoL). Improving the QoL for people with mental illness is one of the most critical steps in stopping disease progression and avoiding complications of mental illness. Therefore, we aimed to assess the QoL and its determinants in patients with mental illness in outpatient clinics in Northwest Ethiopia in 2023. Methods A facility-based cross-sectional study was conducted among people with mental illness in an outpatient clinic in Ethiopia. The sampling interval was decided by dividing the total study participants who had a follow-up appointment during the data collection period (2400), by the total sample size 638, with the starting point selected by lottery method. The interviewer-administered WHOQOL BREF-26 tool was used to measure the quality of life (QoL) of people with mental illness. The domains of QoL were identified, and indirect and direct effects of variables were calculated using structural equation modelling with SPSS-28 and Amos-28 software. A p-value of < 0.05 and a 95% CI were used to evaluate statistical significance. Results A total of 636 (99.7%) participants agreed to participate and completed the data collection. The mean score of overall QoL of people with mental illness in the outpatient clinic was 49.6 ± 10 Sd. The highest QoL was found in the physical health domain (50.67 ± 9.5 Sd), and the lowest mean QoL was found in the psychological health domain (48.41 ± 10 Sd). Rural residence, drug nonadherence, suicidal ideation, not getting counselling, moderate or severe subjective severity, family does not participate in patient care and a family history of mental illness had an indirect negative effect on QoL. Alcohol use and psychological health domain had direct positive effect on QoL. Furthermore, objective severity of illness, having low self-esteem, and having history of mental illness in the family had both direct and indirect effect on QoL. Furthermore, sociodemographic factors (rural residence, illiterate educational status, not married marital status), social support-related factors (poor self-esteem, family not participating in patient care), substance use factors (alcohol use, tobacco use) and clinical factors (high objective and subjective severity of illness, not getting counselling, suicidal ideation, higher number of episodes, comorbid illness, family history of mental illness, poor drug adherence) directly and indirectly affected QoL. Conclusions In this study, the QoL of people with mental illness was poor, with the psychological health domain the most affected. Sociodemographic factors, social support-related factors, drug use factors, and clinical factors, directly and indirectly affected QoL through the mediator variables of physical health domains, psychological health domains, social relation health domains, and environmental health domains. In order to improve the QoL of people with mental illnesses, we recommend that emphasis be given to addressing the QoL of those with mental illness, including the development of policy and practice responses that address the above identified factors.